Traditional timber frame walls: mechanical behavior analysis and retrofitting - Vasconcelos, Graça (2015)
Timber frame construction is characteristic of several historic city centres as well as of vernacular architecture in several countries around the world, either motivated by the availability of materials and construction traditions or by the need of reducing the seismic vulnerability of buildings, namely in south European countries, where this construction technique was adopted for seismic-resistance purposes. From past earthquakes, it has been seen that timber frame construction can be viewed as an interesting technology as it has exhibited a very reasonable behaviour when compared to other traditional construction techniques such as masonry walls. This chapter provides an overview of the main insights on the seismic performance of timber frame buildings from the evidences of past earthquakes and provides the main results of recent research focused on the in-plane cyclic behavior of timber frame walls with distinct geometrical configurations. Additionally, the main seismic performance indexes of timber frame walls, both unreinforced and retrofitted, are presented and discussed in detail.